PRODUCT INNOVATION STRATEGY AND MARKETING TRANSFORMATION IN IMPROVING THE COMPETITIVENESS OF MSMES: A CASE STUDY OF VSPORT SUKABUMI - Denis Ramadia; Abu Bakar Ashidiqy; Bagja Rahma Putra (RADJA PUBLIKA, 2025)
This study aims to analyze the product innovation strategies and marketing transformation implemented by the UMKM VSPORT Sukabumi in enhancing its business competitiveness amidst increasingly intense market competition. VSPORT is a micro-enterprise engaged in the manufacturing of sports balls and has introduced various innovations such as product design development, improvement of raw material quality, and enhanced packaging. Additionally, VSPORT has transformed its marketing approach from conventional methods to digital marketing by using marketplace platforms such as Shopee, Tokopedia, and TikTok Shop. This research adopts a qualitative approach using a case study method, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the combination of product innovation and digital marketing contributes positively to increased sales volume, market expansion, brand image enhancement, and operational efficiency. These results indicate that the right innovation strategy, when synergized with digital marketing transformation, can sustainably improve MSME competitiveness while empowering local communities through job creation and grassroots economic development.